ANALYSIS OF STUDENTS' COGNITIVE STYLE ACCORDING TO WITKIN IN SOLVING PYTHAGORAS PROBLEMS - Kaliky, Syafruddin; Khan, Nusrat Ali (IAIN Ambon, 2023)
Cognitive style is a way of thinking that students use to help solve a problem according to their knowledge and experience. This research aims to determine students' cognitive styles in solving Pythagorean problems. The subjects in this research were students who met the FI and FD cognitive styles based on the GEFT test. This research was carried out in class VII of MTs Nurul Ikhlas Ambon. The method used in this research is descriptive with a qualitative approach. The research results showed that FI students use different methods according to their knowledge, and the solutions they carry out tend to be unstructured. The method FI students use is a fast way to solve Pythagorean problems. Apart from that, the images created by referring to the information obtained are done simply by the concepts understood. Meanwhile, FD students use the same method their previous teacher taught. The solving process is carried out in a structured manner to obtain the final result. The method used by FD students is the Pythagorean formula. Furthermore, in making pictures, FD students clearly describe the information in the problem in detail and complexly.